2022
DOI: 10.1016/j.arthro.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hip Microinstability: Understanding a Newly Defined Hip Pathology in Young Athletes

Abstract: Microinstability is an increasingly recognized diagnosis in young athletes presenting with hip pain. Causes of microinstability may include abnormality of the hip bony anatomy, acetabular labral tears, joint capsule laxity or injury, and muscle dysfunction. Borderline hip dysplasia is an increasingly recognized factor predisposing to microinstability. The capsuloligamentous structures of the hip, particularly the iliofemoral ligament, provide important restraints to femoral head motion, and iatrogenic defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Hip microinstability, or atraumatic hip instability, is increasingly recognized as a contributing factor in non‐arthritic hip pain and disability in young patients and athletes [3, 7, 14, 26]. Microinstability can be defined as extraphysiologic motion or pathological laxity that leads to symptomatic abnormal mechanics of the hip [14, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Hip microinstability, or atraumatic hip instability, is increasingly recognized as a contributing factor in non‐arthritic hip pain and disability in young patients and athletes [3, 7, 14, 26]. Microinstability can be defined as extraphysiologic motion or pathological laxity that leads to symptomatic abnormal mechanics of the hip [14, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study did not evaluate demographic or physical examination variables that have been correlated with microinstability. 14-16,40 However, previous data have demonstrated that atraumatic microinstability is associated with less articular cartilage damage compared with cam deformity FAIS. 1 Therefore, it is unlikely that this limitation would confound the study results.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 69 patients with isolated hip microinstability (without bony FAI morphology) based on previously published intraoperative criteria (ease of hip distraction, residual hip subluxation after release of traction, straight anterior or lateral chondral and labral pathology). 4,6,7,14,15,22,26 The force required for hip distraction was measured based on a consistent and standardized method, recorded as the number of turns of traction (1 turn ¼ 4 mm of axial traction) to obtain 10 mm of hip distraction, as has been previously reported. 6 The initial state was obtained by placing the patient firmly against a perineal post with body weight traction applied by the senior surgeon as previously described.…”
Section: Study Groupsmentioning
confidence: 99%